Total Asam, pH, dan Karakteristik Mikrobiologi Minuman Kombucha dari Daun Takokak (Solanum torvum Swartz.) sebagai Produk Pangan Fungsional - Wijaya Putra, Anak Agung Ngurah Dwi Ariesta; Yoga, Wahyu Krisna; Fitriani, Pande P. Elza (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 14 No 1 (2025): Jurnal ITEPA, 2025)
Public awareness of the importance of functional food is increasing, this has encouraged researchers and the food industry to encourage the production of food products that have health functions for the body. One food product that has an impact on health is the kombucha drink. Kombucha drinks usually come from tea leaves. The takokak plant (Solanum torvum Swartz) or known in Bali as tuwung cockak is a plant from the Solanaceae tribe which is spread across South and Southeast Asia. The phytochemical content of this plant is phenol, flavonoids and tannins which are found in the fruit, seeds, skin and leaves. The aim of this research was to determine the pH value, total acid, total yeast, and total lactic acid bacteria from the takokak leaf kombucha drink during fermentation. The method used was a completely randomized design with 21 samples with a fermentation time of 0 days to 18 days. The results of this research show that the pH value continues to decrease while the total acid level continues to increase. Total yeast and lactic acid bacteria obtained the highest numbers at T3 (6 days of fermentation), but after that experienced a drastic decline. Keywords: kombucha, takokak, fermentation, pH, functional food